Driving Factors Influencing Watershed Management and Sustainability: A Systematic Review - Taslim, Ivan; Basuni, Sambas; Purwanto, Moh. Yanuar Jarwadi; Santikayasa, I Putu (Indonesian Journal of Environmental Management and Sustainability, 2025)
Watershed management and sustainability have gained significant global attention due to escalating environmental, socioeconomic, and governance challenges. This study presents a Systematic Literature Review (SLR) aimed at identifying and synthesizing key driving factors that influence watershed management and sustainability. A comprehensive search was conducted exclusively in the Scopus database, covering publications from 2013 to 2023. Through PRISMA-based screening and thematic analysis of 193 relevant studies, a total of 37 driving factors were identified. These factors were classified into three main domains: biophysical (7 factors), socio-economic (13 factors), and institutional (17 factors). The findings reveal that institutional factors are most prominently emphasized, followed by socio economic and biophysical dimensions. This synthesis provides a holistic understanding of the complex and interconnected elements that drive watershed sustainability. The insights derived are intended to inform future research, support evidence-based policymaking, and strengthen integrated watershed management practices across diverse geographic and socio-political contexts. The search employed multiple keyword combinations, including ”watershed”, ”catchment”, ”river basin”, ”drivers”, ”influencing factors”, and ”determinants”, ensuring broader thematic coverage within the Scopus database.